Pengalaman Anggota Keluarga Mendampingi Lansia Penderita Covid-19 Saat Isolasi di RSU Sembiring Deli Tua - Tarigan, Herri Novita; Afrizal; Andani Eka Putra; Adang Bachtiar (Jurnal Kesehatan Komunitas, 2024)
Elderly individuals are the most vulnerable group affected by Covid-19. Anxiety among the elderly regarding Covid-19 is an important mental health factor that needs to be addressed. There are obstacles to meeting the basic needs of the elderly, so they require family assistance. The experience of families in caring for elderly individuals exposed to Covid-19 is very useful for obtaining information related to their care. The purpose of this study is to gain in-depth information about the experiences of family members when accompanying elderly individuals exposed to Covid-19 during isolation in hospitals. This research is qualitative, with a phenomenological approach. Participants consisted of 11 family members selected through purposive sampling, and in-depth interviews were conducted for data collection using five open-ended questions recorded via audio. Data analysis employed content analysis. The findings revealed seven themes: 1) Knowledge of caregivers about the purpose of assisting elderly Covid-19 patients during hospital isolation, 2) Family feelings when their parent is diagnosed with Covid-19, 3) The condition of the elderly after being diagnosed with Covid-19, 4) Activities of caregivers while accompanying elderly Covid-19 patients, 5) Moments when nurses motivate elderly patients with Covid-19, 6) Challenges faced by caregivers during the isolation of the elderly in hospitals, 7) Expectations for caregivers to assist elderly Covid-19 patients during hospital isolation. It is crucial to explore the experiences of families in supporting elderly Covid-19 patients during hospital isolation to provide psychological comfort, which can accelerate their recovery. The presence of family support for elderly Covid-19 patients not only alleviates anxiety and fear but also fosters hope and motivation when they learn of their positive Covid-19 status, especially if they have underlying health conditions. Positive and impactful activities by family members during isolation include continuous communication with the elderly, providing motivation for their recovery, monitoring their nutritional intake, praying, watching shows together, and communicating through phone calls or video calls with other family members at home.